Intervenção: suporte para cuidadores de doentes crônicos através do ensino - Altafim, Letícia Zanetti Marchi (2007)
Considering the highest increasing of the elderly population in our country and simultaneously the increasing of morbidity rate of chronic-degenerative disease, in general, there are people seeking to be in attendance, at day centre or hospital; these people are dependents on and when come back home, need familial caregivers. The caregivers are the fundamental importance to keep the patient in his community, to prevent and treat the problems caused by the stress factors among them must contribute to reduce or to postpone the hospitalization of caregivers. Besides, the improvement on quality of life could give the caregivers do better help to patients by influencing positively on the chronic disease course. So, this research try to undestand the reality of the caregivers lifes who s relatives are chronic illnesses pacientes. With this knowlege, implement and evaluate the effectiveness of an intervention proposal with caregivers. The objective of this intervention is to attenuate the happened stress conditions of the care activities. The research will use interview with caregivers at USE, at Federal University at S.Carlos; this interview will be taped and latter, a transcription to analyze the content of answers and to elaborate the intervention plan, in that case, a course. The course will consist of informative aspect about disease and daily life activities, as well as, formative aspect about self knowledge. A quality of life instrument named Caregiver Burden Scale will be given to caregivers. After the intervention (course) the Scale will be give once more to verify the date and to check the efficacy of intervention.